CORRIGENDUM TO NEW INEQUALITIES ON HOMOGENEOUS FUNCTIONS, J. INDONES. MATH. SOC. 15 (2009), NO. 1, 49-59 - Lokesha, L; Nagaraja, K M; Simsak, Y (IndoMS, 2015)
This is corrigendum to New Inequalities on Hoomogeneous FunctionsDOI :Â http://dx.doi.org/10.22342/jims.21.1.201.71-72